Effects of stress coping and emotion regulation on student academic stress - Sari, Permata; Bulantika, Siti Zahra; Dewantari, Tri; Rimonda, Rubi (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2020)
This study aims to determine the effect of stress coping and emotion regulation on student academic stress. This study is an expos facto study with a sample of semester IV Islamic counseling guidance students of UIN Raden Intan Lampung, as many as 150 students, samples taken by the purposive method. The instruments used in this study were stress coping scale, emotion regulation scale, and academic stress scale, which had been developed based on indicators and had been validated. The analysis used in this study is the multiple regression analysis. The results of the study indicate that stress coping and emotional regulation have a significant effect on student academic stress.